Respuesta :

Answer:

-7/2

Step-by-step explanation:

-4(-2u+3)-u=3(u-7)-5

8u-12-u=3u-21-5

8u-u-12=3u-26

7u-12=3u-26

7u-3u-12=-26

4u-12=-26

4u=-26+12

4u=-14

u=-14/4

simplify

u=-7/2

Hi1315

Answer:

u = - 3.5

Step-by-step explanation:

Before solving this you have to know that,

(-) × (-) = (+)

(-) × (+) = (-)

(+) × (+) = (+)

Let us solve now.

[tex]-4(-2u+3)-u=3(u-7)-5[/tex]

[tex]8u-12-u=3u-21-5[/tex]

[tex]7u-12=3u-26[/tex]

[tex]7u-3u=12-26[/tex]

[tex]4u=-14[/tex]

[tex]\frac{4u}{4} = \frac{-14}{4}[/tex]

[tex]u=-3.5[/tex]

Hope this helps you.

Let me know if you have any other questions :-)